ANALISA PERBANDINGAN LAPORAN KEUANGAN DAN RASIO KEUANGAN SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA KOPERASI KARYAWAN SUCOFINDO (KOPERASI SUCOFINDO JAYA) TAHUN 2009 – 2011 - Pramudena, Sri Marti (STIE Binaniaga, 2013)
This study aims to determine the financial position and financial performance Cooperative Sucofindo Jaya (KOPSUCOFINDO JAYA) from fiscal year 2009-2011 through a comparative analysis / comparisons and ratio analysis. From the research, the authors obtained a picture that results of the financial position and financial performance of KOPSUCOFINDO JAYA as follows: (1) To Horizontal Analysis of the Balance Sheet shows the overall unfavorable developments as the rise of short-term debt experienced a greater percentage increase than the increase in current assets (2) For Horizontal Analysis of the SHU, SHU in 2010 an increase of 125.38% compared to 2009 and in 2011 increased by 282.47% compared to 2009, but this increase was not followed by a reduction in the burden of cost of goods, especially business and this increase was obtained from the contribution percentage increase in other income. (3) For Vertical Analysis of the Balance Sheet shows that in terms of assets, current assets are assets that make up the largest component but also cause considerable investment value embedded in current assets and also showed asset turnover, receivables turnover and working capital is very low under 1 times. (4) For the SHU Vertical analysis shows that income JAYA KOPSUCOFINDO more than 85% absorbed in the Cost of Goods. (5) For liquidity analysis showed that highly liquid KOPSUCOFINDO JAYA obtain an average value above 400%. (6) For solvency analysis shows that the performance is not good / not solvable because the results of the analysis LITA average of above 95%, Total Debt to Equity Ratio in the top 2.000%, and Net Worth Debt Ratio to average below 4%. (7) For activity ratios indicate that the performance is not good for Turnover of Assets value of 1 times. (8) For the rentability analysis KOPSUCOFINDO JAYA show results for ROA of 0.86% (2009), 1.31% (2010), 1.18% (2011), ROE in 2009 is 14.81%, 26.43% in 2010 and 2011 amounted to 31.11%, for the ROI of 0.56% in 2009, in 2010 was 0.96% and by 0.93% in 2011. (9) For the analysis of profitability, for the analysis of GPM in 2009 amounted to 1.49%, in 2010 of 2.31% and 3.92% in 2011. As for the analysis of NPM in 2009 amounted to 0.97%, in 2010 by 1.70% and by 3.10% in 2011. Keywords: Cooperative Financial Performance, horizontal analysis, vertical analysis, Analysis of Liquidity, Solvency Analysis, Activity Analysis, Profitability Analysis, profitability analysis